HIV Status and Psychosexual Problems among Young Adults in Togo - Dodji, AKAMAH Kodjo; Boussanlègue, TCHABLE; Mofou, BELO (Journal of Social Work and Science Education, 2021)
This research verified the link between HIV status and sexual problems in young adults. Based on the results of our study following the administration of the self-assessment questionnaire on sexual problems (male and female), we came to the conclusion that HIV-positive status causes more sexual problems, particularly among young men. Despite the problems of vaginal dryness and painful coitus observed in HIV-positive young women, we can say that HIV-positive young women do not generally have sexual problems that interfere with sexual activity.